Doses and application times of trinexapac-ethyl in upland rice - Trindade Martins, Juliana; Arf, Orivaldo; Constantino Meirelles, Flávia; Mendes dos Santos Lourenço, Flávia; Martins Silva, Vinicius; Leal do Nascimento, Matheus Vinícios (Revista Ceres, 2025)
The use of growth regulators as a technique that can reduce plant height and thus strengthen stalks, which may be an option to eliminate or reduce plant lodging, thereby avoiding crop loss. However, there is a lack of information on the subject. The purpose of this study was to evaluate the effect of the dose (0; 37.5; 75.0; 112.5 e 150.0 g ha-1 active ingredient) and the application times of trinexapac-ethyl (sixth, seventh and eighth leaves), in a randomized complete block, in a 5x3 factorial scheme, with four replicates. The field experiment was performed during the 2016/17 crop season, in the experimental farm located in Selvíria, Mato Grosso do Sul State, Brazil, at Universidade Estadual Paulista - UNESP, Ilha Solteira, São Paulo State, Brazil – Campus. It is not recommended to apply the trinexapac-ethyl at eighth leaf, especially in the doses of 75.0; 112.5 and 150.0 g ha-1, since they generated the lowest values for yield parameters, thus reducing productivity, and providing greater number of unfilled grains. Taking into account the reduction in plant height, the minimization of lodging and grain yield, trinexapac-ethyl should be applied to the seventh leaf of the BRS Esmeralda rice at the dose of 75 g ha-1.